Equatorial plasma bubbles features over the Brazilian sector according to the solar cycle and geomagnetic activity level - Carmo, C. S.; Dai, L.; Denardini, C. M.; Figueiredo, C. A. O. B.; Wrasse, C. M.; Resende, L. C. A.; Barros, D.; Moro, J.; Chen, S. S.; Picanço, G. A. S.; Silva, R. P.; Wang, C.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Equatorial plasma bubbles (EPBs) can lead to signal degradation, affecting the measurement accuracy. Studying EPBs and their characteristics has gained increasing importance. The characteristics of EPBs were investigated using the rate of total electron content (TEC) index (ROTI) maps under different solar and magnetic activity conditions during two periods: July 2014–July 2015 (solar maximum activity with F10.7: 145.9 × 10−22 W⋅m−2⋅Hz−1) and July 2019–July 2020 (solar minimum activity with F10.7: 69.7 × 10−22 W⋅m−2⋅Hz−1). We also divided this analysis according to the magnetic activity levels based on Kp and Dst (disturbance storm time) indices, classified as follows: quiet+ (Kp ≤3 and Dst >−30 nT), quiet− (Kp ≤3 and Dst <−30 nT), disturbed weak (−50 nT <Dst ≤−30 nT), moderate (−100 nT <Dst ≤−50 nT), and intense (Dst ≤−100 nT). The ROTI is calculated using the slant TEC with the carrier phase, and its keograms are used to extract the zonal velocity and distance. Our statistical investigation shows the occurrence rate, duration, zonal drift velocity, and inter-bubble zonal distance of EPBs over the Brazilian sector. The latitudinal extension and zonal drift velocity of EPBs are higher during the solar maximum than those in the solar minimum. In addition, EPBs are found with unusually long durations, remaining until the morning (∼12 UT), and 10% of EPB observations occurred on the winter solstice.